Experimental pulmonary aspergillosis in calves with application of bronchoscopic techniques - PAWAIYA, R V S; CHARA, KALI; SIKDAR, A (The Indian Journal of Animal Sciences, 2013)
Pulmonary aspergillosis was induced in 2 groups of calves by intrahronchial inoculation of Aspergillus fumigatus spores and mixture of spores and mycelia @ 20 ml (3.4 x 108 spores/ml in hoth inocula) using hronchoscope without anaesthesia, Bronchoscopic procedures (bronclioalveolar lavage, brush cytology and lung biopsy) were employed to evaluate their diagnostic applicahility in calves. The hiopsy specimens evinced polymorphonuclear cells initially followed by mononuclear and cpithelioid cell predominance in spores-treated group 2 while mixed cellular reaction followed by lymphocytic infiltration was the main feature in spores + mycelia-treated group 3, On necropsy, pmgressive severity of lesions was noticed grossly at various stages in both the groups excepting in 3 surviving calves of group 3. Microscopically, haemorrhagic lesions at 12 DPI, mononuclear aggregates at 17 DPI, and granulomatous discrete lesions from 19 to 39 DPI were ohserved in group 2. In group 3 mixed reactiom at 8 DPI with dcvelupment of granulomatous lesions at 12 and 16 DPI were evident. Branched fungal hyphae were demonstrable in granulomas in both the infected groups. The disease course was prolonged in spores-treated group but Was shorter with early culmination into chronicity of the lesions in sporcs + mycelia-treated group. Bronchoscopic techniques were considered helpful in the early diagnosis of pulmonary aspergillosis in calves,